Numerical Investigation of a Solar PV/T Air Collector Under the Climatic Conditions of Zarqa, Jordan - Salem Nijmeh; Ahmad Ibrahim Bani Yaseen; Moh'd Sami Ashhab; Mohammad Juaidy (International Journal of Renewable Energy Development, 2022)
The use of hybrid photovoltaic/thermal (PV/T) and low concentrating photovoltaic/thermal (LCPV/T) systems can significantly enhance the overall solar energy conversion efficiency by delivering electricity and thermal energy. This paper presents a case study using a standing PV system's theoretical and modeling approach that can be modified to adapt to the hybrid technology. Firstly, a single-pass conventional PV/T air-cooled collector is investigated based on heat transfer and electrical models under the climatic conditions of Zarqa, Jordan. The performance parameters are evaluated using thermal and electrical properties of the considered PV installation and measured meteorological data. Results show that the total energy produced varies between a maximum of 134.6 kWh/m2 in July and a minimum of 81.7 kWh/m2 in January. The annual average hourly variation of overall energy efficiency ranges between 79.2% and 88.4%. Moreover, the dissipated thermal energy can meet 63.6% of the total energy required to ventilate the Hashemite University Presidency Building during the winter months. Finally, the performance of the modeled PV/T system air system coupled with flat boosters to provide a low irradiation concentration ratio (CR) is explored. The maximum electric output of the resulting LCPV/T system is compared with the uncooled system. It is found that the percentage improvement due to air cooling ranges between 0.72% at CR=1 and 2.77% at CR=2.5